CONTROL AND LIABILITIES OF REGIONAL GOVERNMENT OF RIAU PROVINCE AS THE SHAREHOLDER OF PROVINCIALLY-OWNED ENTERPRISE BANK IN PEKANBARU CITY BASED ON LAW NUMBER 40 OF 2007 ON LIMITED LIABILITY COMPANIES - Irriansyah Irriansyah; Irfansyah Irfansyah; Rezmia Febrina (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2021)
What are the liabilities of regional government of Riau Province as shareholders in provincially-owned enterprise Bank based on provisions of Law Number 40 of 2007 on Limited Liability Companies? How is Control by regional government of Riau province as a shareholder in a provincially-owned enterprise Bank according to provisions of Law Number 40 of 2007 concerning Limited Liability Companies? Purpose of this study is to explain and analyze the liabilities of regional government of Riau province as shareholders in provincially-owned enterprise bank and to explain Control by the Regional Government of Riau Province as Shareholders in provincially-owned enterprise bank according to provisions of Law Number 40 of 2007 on Limited Liability Companies. Type of this research is sociological legal research. From results of this study, liabilities of shareholders is limited to the capital (shares) invested or owned or in other words, shareholders are not personally responsible for agreements made on behalf of company and are not responsible for the company's losses in excess of shares they owned, shareholders are personally responsible for the losses of a limited liability company, if requirements of limited liability company as a legal entity have not been or are not fulfilled, bad faith to take advantage of company solely for personal interests and, shareholders are involved in unlawful acts using the company's assets which resulted in company can’t pay off company's debt, limited liability company of provincially-owned enterprise bank is a limited liability company which is partially closed. Shares in the Bank can be owned by many parties, in this case provincial government and regency/city governments within the province. With the conclusion that the shareholder is not personally responsible for the action made on behalf of company and is not responsible for the company's losses in excess of the shares owned,.